Synopsis: Public investment prioritization for Rwanda's agricultural transformation: Benefits of an increase in public spending on agriculture under PSTA4 - Aragie, Emerta A.; Diao, Xinshen; Spielman, David J.; Thurlow, James; Mugabo, Serge; Rosenbach, Gracie; Benimana, Gilberthe Uwera (International Food Policy Research Institute, 2022)
Although public spending under the fourth Strategic Plan for the Transformation of Agriculture 2018– 2021 (PSTA 4) is generally well structured and cost-effective, funding has been largely stagnant— and even declining, when measured in constant prices—during PSTA’s first four years. This note summarizes the effects of a modest reallocation of public spending under PSTA 4 towards greater cost-effectiveness, as well as a modest increase in PSTA 4 spending. Results draw on an economywide modeling tool designed to prioritize public resources around four key development goals: economic growth, employment creation, poverty reduction, and diet quality improvement.